Estudo de caso: cenas de atenção conjunta entre mãe ouvinte e bebê surda - Nogueira, Priscilla Andrade Souza (2017)
This research aims at analyzing the functioning of joint attention in the interactions of a deaf baby and his hearing mother that not uses the Brazilian Sign Language (LSB). This is a case study of qualitative and longitudinal nature. We chose as the basis of studies Tomasello (1997, 1999, 2003, 2007) and Kendon (1985) to the field of joint attention and of multimodality on interaction. In this same perspective, we understand the cultural impact on human development as a parameter of human interactions (VYGOTSKY, 1978), and we adopt the studies on language acquisition and interaction by children performed by Cavalcante (1994, 1999, 2012). For methodological purposes we did periodic filming of moments of interaction between a listening mother and her deaf baby aged 17 to 22 months for 6 (six) months in family home settings. From the filming were selected the scenes where the joint attention between the dyad occurred in order to make the transcriptions of the data and its analysis. The ELAN program was used as a tool for transcripts. For the analysis of the data, we choose the categories: face to face, joint attention and multimodal resources constituted between mother listener and deaf baby in interactive situations hoping to detect the contributions of these elements in the interaction between people who do not speak the same language. As results we have that the deaf baby engages in contexts of joint attention, produces and responds to multimodal resources, as well as hearing children and these elements aid in the interaction between the hearing mother and the deaf baby